UTILIZATION OF HEC-RAS 2D FOR FLOOD INFLUENCE MODELING DUE TO PEAK DISCHARGE OF WALANAE RIVER IN WAJO DISTRICT - Latif, Fausiah; Hakim, Abdul (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
On December 25, 2024, a flood disaster struck Sabbangparu Sub-district, Wajo Regency, South Sulawesi, caused by heavy rains that persisted for several days. This led to the overflow of the Walanae River and additional flooding from neighboring regencies. The disaster affected thousands of residents, submerged agricultural lands, and completely cut off several access roads. This study conducted a simulation aimed at predicting flood-affected areas due to the overflow of the Walanae River in Wajo Regency as part of future disaster mitigation efforts. The simulation utilized HEC-RAS 6.4.1 software, which has the capability to model 1D and 2D fluid flow. Additionally, flood-affected area analysis was performed using ArcGIS 10.8. The flood map simulation results indicated that the affected area covered 10,814.35 hectares, equivalent to 68.22% of the administrative area of Sabbangparu Sub-district. The river cross-section simulation revealed that most of the Walanae River cross-sections were unable to accommodate the peak discharge of 3,658.4 m³/s, causing water to overflow into residential areas and rice fields. This poses the risk of significant economic losses and even fatalities. The results of this study are expected to serve as a reference in planning future flood disaster mitigation efforts.